Are hybrids between Atlantic salmon and brown trout suitable long‐term hosts of Gyrodactylus salaris during winter?. Issue 10 (20th January 2017) - Knudsen, R; Henriksen, E H; Gjelland, K Ø; Hansen, H; Hendrichsen, D K; Kristoffersen, R; Olstad, K
Abstract: The monogenean parasite Gyrodactylus salaris poses serious threats to many Atlantic salmon populations and presents many conservation and management questions/foci and challenges. It is therefore critical to identify potential vectors for infection. To test whether hybrids of native Atlantic salmon ( Salmo salar ) × brown trout ( Salmo trutta ) are suitable as reservoir hosts for G. salaris during winter, infected hybrid parr were released into a natural subarctic brook in the autumn. Six months later, 23.9% of the pit‐tagged fish were recaptured. During the experimental period, the hybrids had a sixfold increase in mean intensity of G. salaris, while the prevalence decreased from 81% to 35%. There was high interindividual hybrid variability in susceptibility to infections. The maximum infrapopulation growth rate (0.018 day −1 ) of G. salaris throughout the winter was comparable to earlier laboratory experiments at similar temperatures. The results confirm that infrapopulations of G. salaris may reproduce on a hybrid population for several generations at low water temperatures (~1 °C). Wild salmon–trout hybrids are undoubtedly susceptible to G. salaris and represent an important reservoir host for the parasite independent of other co‐occurring susceptible hosts. Consequently, these hybrids may pose a serious risk for G. salaris transmission to nearby, uninfected rivers by migratory individuals.